Pendampingan Pemberdayaan Tanaman Aquaponik Masyarakat Perum Emerald Garden Bumiayu - Viajeng Purnama Putri; Novita Ratna Satiti; Sri Nastiti Andharini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aquaponic plant empowerment mentoring program at Emerald Garden Housing, Bumiayu, aims to improve community skills and welfare through environmentally friendly cultivation technology. Aquaponics is a system that combines the cultivation of fish (aquaculture) and plants (hydroponics) in a mutually beneficial environment. This activity includes several stages, namely socialization, training, technical assistance and evaluation. The methods used include outreach, direct demonstrations, and field practice involving all residents. The program results show an increase in community knowledge and skills in managing aquaponic systems, as well as a significant increase in plant and fish production. Apart from that, this program also has a positive impact on improving the household economy and local food security. From the evaluation results, it can be seen that there is high enthusiasm from the community to continue developing and utilizing this aquaponic technology. This program has succeeded in creating a sustainable community empowerment model that can be replicated in other areas. The challenges faced include limited land and the need for technical adjustments that require further attention